In Search of the Virgin and Child in Egypt: Coptic Art in Specialized Encyclopedias - Garcia, Larissa (Journal of religious and theological information, 2019)
This article examines a variety of specialized encyclopedias from several disciplines that can be used to introduce students to the topic of Coptic art. The reference works included here can be found in a variety of academic libraries, from Carnegie research institutions to learning resource centers in community libraries, and will help students develop the foundational knowledge necessary to approach more specific topics within Coptic art. Although students may be comfortable, with varying degrees of effectiveness, searching the online catalog or navigating library databases to find books and journal articles, they are, for the most part, unaware of the wealth of useful information found on the metaphorical reference shelves. It is here that librarians can serve a valuable role identifying specific reference titles that introduce students to scholarly texts on a myriad of topics.